Advancing the Sustainable Development Goals through improving eye health: a scoping review. Issue 3 (March 2022) - Zhang, Justine H; Ramke, Jacqueline; Jan, Catherine; Bascaran, Covadonga; Mwangi, Nyawira; Furtado, João M; Yasmin, Sumrana; Ogundo, Cynthia; Yoshizaki, Miho; Marques, Ana Patricia; Buchan, John; Holland, Peter; et al.
Summary: UN member states have committed to achieving the Sustainable Development Goals (SDGs) by 2030. This Review examines the published evidence on how improving eye health can contribute to advancing the SDGs (beyond SDG 3). We identified 29 studies that showed direct benefits from providing eye health services on SDGs related to one or more of poverty (SDGs 1, 2, and 8), education (SDG 4), equality (SDGs 5 and 10), and sustainable cities (SDG 11). The eye health services included cataract surgery, free cataract screening, provision of spectacles, trichiasis surgery, rehabilitation services, and rural community eye health volunteers. These findings provide a comprehensive perspective on the direct links between eye health services and advancing the SDGs. In addition, eye health services likely have indirect effects on multiple SDGs, mediated through one of the direct effects. Finally, there are additional plausible links to other SDGs, for which evidence has not yet been established.